2017
DOI: 10.1021/acs.biochem.7b00446
|View full text |Cite
|
Sign up to set email alerts
|

Horse Liver Alcohol Dehydrogenase: Zinc Coordination and Catalysis

Abstract: During catalysis by liver alcohol dehydrogenase (ADH), a water bound to the catalytic zinc is replaced by the oxygen of the substrates. The mechanism might involve a pentacoordinated zinc or a double-displacement reaction with participation by a nearby glutamate residue, as suggested by studies of human ADH3, yeast ADH1, and some other tetrameric ADHs. Zinc coordination and participation of water in the enzyme mechanism were investigated by X-ray crystallography. The apoenzyme and its complex with adenosine 5′… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
64
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(74 citation statements)
references
References 102 publications
3
64
0
1
Order By: Relevance
“…Furthermore, rate limitation of the catalyzed oxidation of ( S )‐ 1 has been proposed to be mainly coupled to the rate of NADH release from the enzyme, which is of the same magnitude as k cat . Since ADH‐A, like its related isoenzyme from horse liver, follows an ordered sequential Bi–Bi mechanism , the rate‐limiting release of the reduced nucleotide would be unchanged irrespective of which alcohol enantiomer has been oxidized, since the same ketone product would be produced in either case. Also, in an ordered mechanism the rate of nucleotide release only involves the binary E•NADH complex.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, rate limitation of the catalyzed oxidation of ( S )‐ 1 has been proposed to be mainly coupled to the rate of NADH release from the enzyme, which is of the same magnitude as k cat . Since ADH‐A, like its related isoenzyme from horse liver, follows an ordered sequential Bi–Bi mechanism , the rate‐limiting release of the reduced nucleotide would be unchanged irrespective of which alcohol enantiomer has been oxidized, since the same ketone product would be produced in either case. Also, in an ordered mechanism the rate of nucleotide release only involves the binary E•NADH complex.…”
Section: Introductionmentioning
confidence: 99%
“…Most interestingly, a mechanism involving a hemi labile ligand and double displacement and inversion of the pyramid at a Td Zn II centre has been proposed for substrate binding and product release in some enzymes. In Horse Liver Alcohol Deshydrogenase, [31] it has, for example, been shown that a glutamate residue (Figure 7) participates in a double‐displacement interchange mechanism, via a trigonal bipyramidal geometry. The residue displaces, in a first step, the water molecule bound to the metal ion, and in a second step, the substrate oxygen (an alcohol) displaces the glutamate residue to give rise to the structure observed in the ternary complexes (enzyme/cofactor NAD + /alcohol substrate).…”
Section: Resultsmentioning
confidence: 99%
“…In the case of hydrolytic zinc enzymes, the metal is most often bound to three amino acid residues, generally histidine (His), and a water molecule completes its coordination sphere in a tetrahedral environment [6] . This water molecule can then either be activated by deprotonation, thereby giving rise to a hydroxide ion at physiological pH (such as in carbonic anhydrases), [8] activated by a hydrogen‐bonded general base (e. g., in metallo‐peptidases), [9] or displaced by the substrate (e. g., alcohol dehydrogenases) [10] or an inhibitor [11] . This raises questions relative to the role of water molecules in substrate binding, product release, as well as in inhibitor efficiency when the latter presents a coordinating site.…”
Section: Introductionmentioning
confidence: 99%
“…Contudo, diferentes estudos apontam para um mecanismo muito mais complexo, podendo envolver um átomo de zinco pentacoordenado ou uma reação de duplo deslocamento com a participação de um resíduo glutamato. 58 Estudos realizados com a álcool desidrogenase da bactéria termófila Thermoanerobacter brockii (TbADH), por exemplo, apontaram para dois novos estados do zinco pentacoordenado, TR1 e TR2 (Esquema 14). 59 No primeiro estado (TR1) o Zn está coordenado a uma molécula de água e aos resíduos His59, Cys37, Asp150 e Glu60.…”
Section: Desidrogenasesunclassified